Formal Friendship, Real Suspicions: Diplomatic Relations between Mexico and South Korea, 1962-1987 - León-Manríquez, José Luis (México y la Cuenca del Pacífico, 2015)
This article deals with the initiation and development of diplomatic relations between Mexico and the Republic of Korea. Both countries started relations in 1962, but in a rather idiosyncratic way. While South Korea immediately opened an embassy and appointed a resident ambassador, Mexico made a deliberate effort to keep bilateral contacts to a bare minimum. Thus, Mexico only opened its embassy in Seoul in 1978 and posted a resident ambassador until 1987. The text addresses the explanation of this asymmetric relation, positing as main hypothesis that, given the antiimperialist lineages of its revolution, Mexico sought to establish a distance from the international positions of the United States. This position did not entail, however, a preference for the dprk. The situation would change over time. The successive détentes between the great powers in the 1970s and 1980s, the tensions between Mexico and North Korea due to Pyongyang’s support of a Mexican guerrilla group, and the increased social, cultural and economic links between the two countries were the main factors for overcoming such distrust. Resumen: En el presente artículo se estudia el desarrollo inicial de las relaciones diplomáticas entre México y la República de Corea. Ambos países comenzaron su relación en 1962, pero de una manera muy peculiar. Mientras que Corea del Sur abrió inmediatamente una embajada y nombró un embajador residente, México hizo un esfuerzo deliberado para mantener los contactos bilaterales al mínimo indispensable. Así, México sólo abrió su embajada en Seúl en 1978 y nombró a un embajador residente hasta 1987. El texto busca explicar esta relación asimétrica, planteando como hipótesis principal que, habida cuenta de los linajes antiimperialistas de su revolución, México trataba de establecer una distancia respecto a las posiciones internacionales de Estados Unidos. Esta posición no implicaba, sin embargo, una preferencia por la RPDC. La situación cambiaría con el tiempo. Las sucesivas detentes entre las grandes potencias en los años setenta y ochenta, las tensiones entre México y Corea del Norte debido al apoyo de Pyongyang a un grupo guerrillero mexicano, y los crecientes vínculos sociales, culturales y económicos entre los dos países fueron los principales factores para la superación de esa desconfianza.